JAMINAN KESEJAHTERAAN HARI TUA BAGI PEGAWAI NEGERI SIPIL PERSPEKTIF HUKUM ISLAM: Studi Kota Jayapura - Fadhel, Muhammad; Basri, Halimah; Mustafa, Adriana (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
The pension fund program is one of the efforts to improve the welfare of Civil Servants who have entered retirement for their service and dedication to the country. This study aims to analyze how the welfare of old age for Civil Servants in Jayapura City Islamic Law Perspective. The type of research used is qualitative research (field research) with juridical and normative syar'i approaches, data sources in the form of primary and secondary data obtained through observation, interviews, documentation and literature studies. The results showed that Civil Servants who have entered retirement will receive pension funds through two main programs, namely the Tabungan Hari Tua program and dana pensiun managed by PT. Taspen Jayapura City Branch, the pension scheme aims to provide income continuity, especially to meet daily needs in old age. Security of the necessities of life is an aspect of concern in Islam, even one of the principles of maqashid al-shari'ah is the obligation to maintain property (economic ability) in addition to the obligation to maintain religion, soul, reason, and offspring.